The importance of rehabilitation in the treatment of breast cancer - Kamusińska, Elżbieta; Ciosek, Marta; Karwat, Irena D. (Medical Studies/Studia Medyczne, 2014)
Mastectomy due to breast cancer results in many problems and physical dysfunctions related with the constant necessity to protect the upper extremity at the site of the operated breast, and application of a specialist physiotherapeutic procedure. Rehabilitation is an integral part of the process of breast cancer treatment, and its primary goal is the limitation of selected physical, psychological, and social consequences of this cancerous disease. The achievement of rehabilitation goals requires teamwork – the simultaneous solving of problems in various spheres of the patient’s life. This work should be considered as overall care activity concerning a human being according to a holistic approach. A very important element of rehabilitation after mastectomy is to reassure the patient that with the help of specialists she can overcome difficulties, solve her problems, and return to normal daily life.